Różnicowanie wysiękowej postaci zwyrodnienia plamki związanego z wiekiem z guzami tylnego bieguna gałki ocznej - Kubicka-Trząska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Many various lesions located in macular region can mimic exudative age-related macular degeneration (AMD), making serious problems in establishing the proper diagnosis. From a practical point of view the most important significance has a differential diagnosis of AMD with posterior pole tumours: choroidal melanoma, choroidal naevus, choroidal haemagnioma and metastatic tumors. The aim of this study is to present, based on literature and our experience, the role of fluorescein and indocyanine green angiography, standard A- and B-scan ultrasonography and colour Doppler ultrasonography in differential diagnosis of exudative AMD and posterior pole choroidal tumours.